Arranjos de antenas para 5G com MIMO em ondas milim??tricas - Boas, Evandro C??sar Vilas (2019)
This work reports the development of slotted waveguide antenna arrays (SWAA), operating in millimeter waves, for multiple-input and multiple-output (MIMO) systems and applied to the fifth-generation mobile networks (5G). Three distinct SWAAs have been proposed for spatial and polarization diversity, by using two identical elements with separation between 3 and 10 ??o. The following performance metrics have been considered: mutual coupling, active reflection coefficient, total active reflection coefficient, correlation coefficient, envelope correlation coefficient (ECC), total radiation efficiency and multiplexing efficiency. A dual-band switched-beam SWAA-based array has been developed for base stations MIMO applications. A second array was implemented to provide sectoral coverage at access points, with elements placed into a case similar of the Apple commercial airport model. Grooved metal structures were applied to the third SWAA to enhance its gain. Excellent agreement between theoretical and measured results has been observed in all cases. The dual-band switched-beam array demonstrated low mutual coupling as low as -36 dB and ECC less than -40 dB for the 28 and 38 GHz operating bands. These parameters were equal to -40 and -50 dB, respectively, for the second array with operation in the 28 GHz band. The high-gain SWAA with metal grooved-structures provided 8.47% (25.54???27.80 GHz) measured fractional bandwidth, gain from 26.6 to 27.7 dBi and half-power beamwidth in the azimuth and elevation planes equal to 10?? and 3??, respectively. The metal grooved-structures enhanced the SWAA gain in 9 dB, resulting in a high-gain array with a simple feeding system.